The Core sets of International Classification of Function and Disability in Physical Therapy - Roohi Abbas, Samreen Sadiq, Ayesha Munawa, Sidra Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
To delineate a common language for describing Functioning and dysfunctioning of individuals with various health condition to be used by health care professionals all over the world, the International classification of function and disability (ICF) also known as ICF model has emerged as a multidimensional classification system which is based on biopsychosocial model of health system1. ICF model addresses many issues related to various disciplines of Rehabilitation specially Physical therapy2. In Physical therapy ICF model is utilized for making decisions ensuring to cover all aspects of human health and functioning, for documentation purpose as well as to enhance communication by agreeing upon the same standardized terminologies2.